Formula supplementation with human and bovine milk oligosaccharides modulates blood IgG and T-helper cell populations, and ex vivo LPS-stimulated cytokine production in a neonatal preclinical model - Monaco, Marcia H.; Wang, Mei; Hauser, Jonas; Yan, Jian; Dilger, Ryan N.; Donovan, Sharon M. (Frontiers in Immunology, 2023)
Introduction: Human milk contains structurally diverse oligosaccharides (HMO), which are multifunctional modulators of neonatal immune development. Our objective was to investigate formula supplemented with fucosylated (2'FL) + neutral (lacto-N-neotetraose, LNnt) oligosaccharides and/or sialylated bovine milk oligosaccharides (BMOS) on immunological outcomes. Methods: Pigs (n=46) were randomized at 48h of age to four diets: sow milk replacer formula (CON), BMOS (CON + 6.5 g/L BMOS), HMO (CON + 1.0 g/L 2'FL + 0.5 g/L LNnT), or BMOS+HMO (CON + 6.5 g/L BMOS + 1.0 g/L 2'FL + 0.5 g/L LNnT). Blood and tissues were collected on postnatal day 33 for measurement of cytokines and IgG, phenotypic identification of immune cells, and ex vivo lipopolysaccharide (LPS)-stimulation of immune cells. Results: Serum IgG was significantly lower in the HMO group than BMOS+HMO but did not differ from CON or BMOS. The percentage of PBMC T-helper cells was lower in BMOS+HMO than the other groups.. Splenocytes from the BMOS group secreted more IL-1β when stimulated ex vivo with LPS compared to CON or HMO groups. For PBMCs, a statistical interaction of BMOS*HMO was observed for IL-10 secretion (p=0.037), with BMOS+HMO and HMO groups differing at p=0.1. Discussion: The addition of a mix of fucosylated and sialylated oligosaccharides to infant formula provides specific activities in the immune system that differ from formulations supplemented with one oligosaccharide structure.